Prevalence of Dental Fluorosis in a City without Fluoridation in its Water Supply: Effect of Sampling - Castilho, Maria Cristina de Matos; Zanin, Luciane; Flório, Flávia Martão (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To determine the prevalence of dental fluorosis in a population not exposed to fluoridated water and to evaluate the effect of the sampling technique on this measurement. Material and Methods: This observational, cross-sectional and quantitative study was conducted in the city of Mariana, Brazil. The participants were selected based on age, so that they had access to fluoridated dentifrice during the formation of the permanent upper teeth. Based on a nominal survey of schoolchildren aged 14 to 19, a probabilistic sample of 304 such children was clinically examined. Dental fluorosis was measured by the Thylstrup-Fejerskov index. The prevalence of fluorosis identified in a previous study, conducted in 2011 in the same city, using the same methodology but employing convenience sampling, was used as a control to compare the effect of the two sampling techniques. Results: The prevalence of dental fluorosis was 3% based on the probabilistic sampling of the subjects. In the previous study, the prevalence of fluorosis was 7% (p<0.05) based on convenience sampling of the same age group. Both studies detected a Thylstrup-Fejerskov fluorosis index value of 1, corresponding to only a mild degree of dental fluorosis. Conclusion: The convenience sampling technique seems to have affected the prevalence of dental fluorosis identified, with a 4% difference between the two studies. The prevalence of dental fluorosis attributed to the use of fluoridated dentifrice in a population not exposed to fluoridation of the water supply was considered low.